Cadê as meninas? Cotidiano e traços de vida de jovens meninas pobres pela perspectiva da terapia ocupacional social - Cappellaro, Mayra (2013)
According field studies of discussions about gender, invisibility of the poor young girls has been a matter for public policy created for youth, but also involves discussions around their cultural manifestations and social participation. The academic scene alerts us to the information that as much the studies on youth as in studies of feminism, there is a large gap in relation to the female juvenile manifestations and further, that the references to them in scientific research takes as focus, in a restrictive manner, adolescence linked to the exercise of sexuality or pregnancy. Trying to deal with this invisibility, we concentrate on the quotidian and terms of life of young people living in a certain suburb, trying the understanding of what actually is being experienced by them, beyond the fact of the limitation of its circulation spaces and access to public equipments, in the direction of the contribution to the establishment of methodologies for intervention on social issues, in relation to this population group. In our professional action, mobilized us in the search for the reasons of the absence of these young people living in public spaces in the city of São Carlos (São Paulo), focusing in a Youth Center. Such mobilization resulted in this master degree research, dealing with an approach that includes the observation-action, depth interviews, in order to gather data to a mapping about who they are, what they think, what they do, what they like and how the young girls live in the suburbs urban. The work has evidenced that youth in question are, in their great majority, hampered in their personal statements. The cultural relations sexist, embodied in an important way in the dynamics of the illegal drug trade, in the men holders of the financial power, in the power of the influence and in the patriarchal system that remains in contemporary society have strongly shaped the future of these young people. Their dreams, desires, social participation and even their personality suffer with the assaults on female autonomy, remaining at some point in the late nineteenth century, before much of what we witnessed over the last century in relation to the rights of women. Our finding indicates that the investments in the social policies specific to this population has been insufficient and that their actions are fragmented and / or inadequate. We concluded that the needs are from several orders, the increased of the general and specific knowledge about this group until the public debate and the social positioning in relation to the guarantee of civil, social and human rights of young Brazilian girls, in order to expand their opportunities of participation and autonomy.